2019
DOI: 10.1002/mrd.23152
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress is involved in lipopolysaccharide‐induced inflammatory response and apoptosis in goat endometrial stromal cells

Abstract: Endoplasmic reticulum (ER) stress is involved in regulating cell metabolism, apoptosis, autophagy, and survival. However, there is not enough information about the role of ER stress in lipopolysaccharide (LPS)‐induced apoptosis and inflammatory cytokine secretion in the uterus. In this study, we found that LPS induced apoptosis and inflammation in goat endometrial stromal cells (ESCs). LPS treatment inhibited cell viability and cell proliferation. In addition, the genes associated with proliferation, such as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…ER stress has been previously implicated in the LPS-induced apoptosis of endometrial stromal cells and overexpression of inflammatory cytokines in the goat uterus ( 8 ). A close association between ER stress and the activation of thioredoxin-interacting protein/NLR family pyrin domain-containing 3 inflammasome has also been validated in a mouse model of LPS-induced endometritis ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ER stress has been previously implicated in the LPS-induced apoptosis of endometrial stromal cells and overexpression of inflammatory cytokines in the goat uterus ( 8 ). A close association between ER stress and the activation of thioredoxin-interacting protein/NLR family pyrin domain-containing 3 inflammasome has also been validated in a mouse model of LPS-induced endometritis ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…LPS is considered to be a trigger of the inflammatory response in bEECs in an in vitro endometritis cell model ( 7 ). In addition, previous in vivo and in vitro studies have revealed that endoplasmic reticulum (ER) stress is involved in the inflammatory response and apoptosis of endometrial stromal cells and mouse uterine tissues ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…The UPR sensors mainly include the protein kinase RNA-like endoplasmic reticulum kinase (PERK), the inositol-requiring enzyme (IRE1α), and activating transcription factor 6 (ATF6). Our previous study showed that ER stress was involved in the infection process of multiple pathogens in goat endometrial epithelial cells (gEECs) through different branches, such as LPS, Brucella, and Trueperella pyogenes [8][9][10]. Meanwhile, studies have reported that there is a close relationship between autophagy and the ER stress pathway, or that the two affect each other [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The UFMylation modification system maintains endoplasmic reticulum homeostasis by regulating the translocation of the nuclear factor kappa B (NF‐κB) protein to the nucleus and stability of inhibitor of NF‐κB (IκB) and inositol‐requiring enzyme 1α (IRE1α), increasing its importance during an inflammatory response (Li et al., 2017; Liu et al., 2017a; Xi et al., 2013). Recent studies indicate that endoplasmic reticulum stress is intimately involved in the occurrence and development of endometritis, an inflammatory disease, and that regulation of endoplasmic reticulum homeostasis reduces its progression, which suggests this could represent a potential target for the prevention and treatment of the disease (Hu et al., 2018; Mohamed et al., 2019; Wu et al., 2018; Yi et al., 2018). Although the pathogenesis of endometritis remains unclear, it has been reported that endoplasmic reticulum stress plays a role in endometritis induced by LPS, and thus, we hypothesize that it may be associated with protein UFMylation (Mohamed et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that endoplasmic reticulum stress is intimately involved in the occurrence and development of endometritis, an inflammatory disease, and that regulation of endoplasmic reticulum homeostasis reduces its progression, which suggests this could represent a potential target for the prevention and treatment of the disease (Hu et al., 2018; Mohamed et al., 2019; Wu et al., 2018; Yi et al., 2018). Although the pathogenesis of endometritis remains unclear, it has been reported that endoplasmic reticulum stress plays a role in endometritis induced by LPS, and thus, we hypothesize that it may be associated with protein UFMylation (Mohamed et al., 2019).…”
Section: Introductionmentioning
confidence: 99%